Are strategies anchored? - Radosveta Ivanova-Stenzel; Gyula Seres (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Anchoring is one of the most studied and robust behavioral biases, but there is little knowledge about its persistence in strategic settings. This article studies the role of anchoring bias in private-value auctions. We test experimentally two different anchor types. The announcement of a random group identification number but also of an upper bid limit in the first-price sealed-bid auction result in higher bids. We show that such behavior can be explained as a rational response to biased beliefs. In Dutch auctions, the effect of a starting price, is negative. We demonstrate that the long-established ranking that the Dutch auction generates lower revenue than the first-price sealed-bid auction crucially depends on the size of the anchor.
Keywords: D44; D91; C72; C91; 330; Anchoring Bias; Games; Incomplete Information; Auctions